The role of educational management in enhancing innovation and problem-solving competencies for students towards global competitiveness: A literature review - Berkat; Setinawati; Basrowi (Social Sciences and Humanities Open)
This research analyzes the contribution of Educational Management in Enhancing Innovation and Problem-Solving Competencies for Students towards Global Competitiveness. The research questions are: 1) What are the main obstacles faced by educational management in efforts to enhance innovation and problem-solving competencies for students in the era of globalization? 2) How can the use of technology in education be optimized by educational management to facilitate the development of innovation and problem-solving competencies for students? Additionally, 3) What are the effective educational management strategies for creating a stimulating learning environment that supports the development of innovative and problem-solving skills for students? This study involves a literature analysis from 2016 to 2023, by searching various academic journals, conference papers, and reliable sources. The research is conducted through different stages, starting with identifying specific and relevant research topics and understanding the background and objectives of the research comprehensively. Data analysis employs qualitative content analysis. Findings indicate that to enhance students' innovation and problem-solving competencies, educational management needs to address existing barriers, optimize the use of technology, and implement effective learning strategies. Educational management needs to adopt a holistic and sustainable approach by involving efficient resource mapping and allocation, advocating for more responsive educational policies, building an organizational culture that supports innovation, and investing in necessary educational technology infrastructure. Optimizing the use of technology involves ensuring equal and equitable access to technology infrastructure for all students and teachers. Designing a curriculum that is relevant and focused on critical, creative, and problem-solving skills. The findings suggest that further research is needed to investigate methodologies in formulating better educational policies and practices.